A Real-time EMG-controlled Functional Electrical Stimulation System for Mirror Therapy - Chen, Yuyang; Dai, Chenyun; Chen, Wei (2019 IEEE Biomedical Circuits and Systems Conference (BioCAS), 2019)
The technique of functional electrical stimulation (FES) has become an essential part of rehabilitation treatment over the last several decades. However, current FES systems are lack of the involvement of subjective intentions from users during the rehabilitation trainings. Accordingly, this article has developed a portable FES hardware system integrated with an EMG-based real-time motor intention classification system to realize the mirror therapy of hand movement for patients with hemiplegia. The EMG signals were collected on the right-hand (sound) side of the forearm and processed to identify the hand motion. Then, the FES system was to activate the electrodes on the left-hand (stimulated) side of the forearm to perform the same movement based the information transmitted by Bluetooth. Validation experiments were performed on two subjects. Six common hand gestures in daily life can be successfully achieved with 100% accuracy. The proposed system with simple design, small size and low cost shows a great promise for the hand rehabilitation training in clinical use.